Analisis Potensi Kebangkrutan Menggunakan Model Altman, Ohlson, dan Zmijewski pada Perusahaan Subsektor Properti dan Real Estate yang Terdaftar di BEI 2017 - 2019 - Lestari, Siti Syafi'ah (JURNAL ACITYA ARDANA, 2022)
Financial distress is a condition before a company goes bankrupt. Financial distress that are not immediately handled will bring the company to a state of bankruptcy. Therefore, an analysis of bankruptcy prediction is needed as early as possible to prevent such bankruptcy. The purpose of this research is to predict bankruptcy of property and real estate companies that listed in Indonesia Stock Exchange for the period 2017 – 2019 using Altman, Ohlson, and Zmijewski models. The data analysis used is quantitative descriptive The sample consists of 7 companies which were determined using purposive sampling. The type of data applied is secondary data, using financial statements for the period 2017 – 2019.. The results showed that Altman, Ohlson, and Zmijewski models gave different results for predicting the bankruptcy. Based on the average value during 2017 – 2019, Altman model predicts 4 companies are bankrupt, 2 companies are not bankrupt, and 1 company in grey area, while Ohlson and Zmijewski models predict that no company will be in a state of bankruptcy.